EGALITARIANISME DALAM TRADISI DAN UPACARA DI DESA KUNO KECAMATAN TEJAKULA KABUPATEN BULELENNG - Suardeyasa, I Gusti Nyoman (PANGKAJA: JURNAL AGAMA HINDU, 2018)
The purpose of this paper is to describe the egalitarianism of traditions and ceremonies that exist in the three villages, for example the ritual development of ceremonial traditions which can still be found to exist today from the ancient conservatives to the already modern adaktif, namely the Julah village, Les Village and Tejakula Village in several aspects related to the tradition of Pitra Yadnya and Sanggah Kemulan ceremonies. The data were collected by observation and literature study. Data analysis was done by descriptive interpretative. The results of this study can be described that: Village Julah perform Atma Wedana ceremony without performing ngabu ceremony. The Sanggah kemulan there is only one palinggih rong telu. Les village performs ceremony pitra yadnya with series of ceremony nyubrahma, matuun, ngalukat until nebas without doing ngabu. Tejakula Village belongs to an adactive village which has conducted mass ceremony of Ngaben. Sanggah Kemulan in Tejakula Village only at his parent house as uwed the origin of the family. Can be concluded tat- twa basically, the essence of the implementation of ceremonial traditions and sanggah kemulan that there exists egaliterianisme between the three.